Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To get the result we have to subsitute h=32 to given equation and solve it.
32=-16t^2+48t /-32
0=-16t^2+48t-32 /*(-1)
0=16t^2-48t+32 /:4
4t^2-12t+8=0 /:4
t^2-3t+2=0
Now we can use delta
delta=b^2-4ac
delta=9-4*2=1
x1=[tex] \frac{3-1}{2}=1 [/tex]
x2=[tex] \frac{3+1}{2}=2 [/tex]
The answer is 1 second and 2 second (when hover and falling down)
32=-16t^2+48t /-32
0=-16t^2+48t-32 /*(-1)
0=16t^2-48t+32 /:4
4t^2-12t+8=0 /:4
t^2-3t+2=0
Now we can use delta
delta=b^2-4ac
delta=9-4*2=1
x1=[tex] \frac{3-1}{2}=1 [/tex]
x2=[tex] \frac{3+1}{2}=2 [/tex]
The answer is 1 second and 2 second (when hover and falling down)
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.